Methenamine as prophylaxis for recurrent urinary tract infections: an overview of the ALTAR trial. Issue 12 (December 2022) - Clarke, Chelsea; Harding, Christopher
Abstract: Current recommended treatment for recurrent uncomplicated urinary tract infections in women includes low-dose daily antibiotics. The UK Antimicrobial Resistance Strategy document underlines the importance of non-antibiotic preventive treatments for common infections such as UTIs. The ALTAR trial investigated the clinical effectiveness of one such non-antibiotic treatment, the urinary antiseptic Methenamine Hippurate in the context of a randomised, open-label, pragmatic, two-arm non-inferiority trial with the comparator of daily low-dose antibiotics. Non-inferiority was confirmed in this study and the authors recommend that it should now be considered as a first-line preventive treatment for recurrent uncomplicated urinary tract infections in women.